2007
DOI: 10.1021/ja074684n
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene-Linked Porphyrin−Fullerene Dyads

Abstract: A new group of porphyrin-fullerene dyads with an azobenzene linker was synthesized, and the photochemical and photophysical properties of these materials were investigated using steady-state and time-resolved spectroscopic methods. The electrochemical properties of these compounds were also studied in detail. The synthesis involved oxidative heterocoupling of free base tris-aryl-p-aminophenyl porphyrins with a p-aminophenylacetal, followed by deprotection to give the aldehyde, and finally Prato 1,3-dipolar azo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 45 publications
(52 reference statements)
4
65
1
1
Order By: Relevance
“…[18][19][20][21][22][23][24] Thus to derive the fullerene-porphyrin conjugates with long chain alkyl substituents we employed the Prato reaction that is 1,3-dipolar cycloaddition to the double bond in a 6,6 ring position in a fullerene of azomethine ylide generated by the condensation of an a-amino acid and an aldehyde. [25][26] The reaction offers the following advantages:…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Thus to derive the fullerene-porphyrin conjugates with long chain alkyl substituents we employed the Prato reaction that is 1,3-dipolar cycloaddition to the double bond in a 6,6 ring position in a fullerene of azomethine ylide generated by the condensation of an a-amino acid and an aldehyde. [25][26] The reaction offers the following advantages:…”
Section: Resultsmentioning
confidence: 99%
“…For a related triad (C 60 + 2 Zn(II) porphyrins) it was shown that the main quenching pathway involved charge-separation from the excited singlet state Zn(II)TPP to the C 60 unit in noncoordinating solvents and from the triplet excited state of Zn(II)TPP in coordinating solvents (El-Khouly et al 2003). Porphyrin-fullerene dyads with an azobenzene linker were synthesized, and the photophysicochemical properties were investigated using steady-state and time-resolved spectroscopic methods (Schuster et al 2007). Photosynthetic models containing dendritic C 60 -H 2 P-(ZnP) 3 conjugates were analyzed in relation to the primary events in photosynthesis, i.e., light harvesting, unidirectional energy transfer, charge transfer, and charge-shift reactions.…”
Section: Donor-acceptor Electron Transfer Compoundsmentioning
confidence: 99%
“…Однако он образует различные по природе диады с молекулами -донорами электронов, таким как тетратиафульвалены, металлоцены, N,N-диметиламинофенил-производные, рутений(II)-трис-бипиридин, порфирины, фталоцианины, являющиеся предметом многочисленных исследований. [2][3][4][5][6][7][8][9][10][11] Значительный интерес представляют порфирин-фуллереновые диады, образованные за счет донорно-акцепторного координационного взаимодействия между электронодонорным атомом заместителя в фуллерене и атомом металла в металлопорфирине. Пиридильные или имидазольные производные пирролидинил- [60] фуллерена имеют дополнительные реакционные центры и могут выступать донорами электронной плотности по отношению к координационно ненасыщенным металлопорфиринам (MP), образуя с ними координационно-связанные диады [12][13][14][15] и молекулярные комплексы более высокого порядка.…”
Section: Introductionunclassified